The School of Energy Policy and Diplomacy of MGIMO - V. I. Salygin (Vestnik MGIMO-Universiteta, 2015)
Nowadays when aspects of global energy security advanced to the forefront and Russia is going to reinforce its leading role in the world energy community, International institute of energy policy and diplomacy (MIEP) organized for the first time in Russia the training of world class experts in the field of energy diplomacy and geopolitics, economics, law, management and public relations, all focused on international energy cooperation. Such energy professionals are extremely sought after by public authorities and international institutions as well as by major international energy companies. MIEP MGIMO is the only study center in Russia and in the whole worlds which is successfully training specialists armed with fundamental academic knowledge and detailed studying of global processes in the sphere of energy diplomacy and geopolitics, international energy cooperation. Alumni of MIEP are outstanding high-caliber professionals who can fluently speak several foreign languages. This day MIEP is a large study, methodic and scientific center ensuring high-quality professional and fundamental training based on the best practices of Russian education as well as on the practices of worldleading universities and business schools.This year International institute of energy policy and diplomacy celebrates its 15th anniversary. This article describes history, evolution of MIEP; unique specific departments and international institutions created in cooperation with prestige European universities; reveals specific features of training of specialists. Soon MIEP plans to accomplish a lot of research and development projects assisted by the best academic staff in close cooperation with international organizations, administrations of the largest petroleum producing regions, top oil and gas corporations-strategic partners (Rosneft, Transneft, Rosseti, Gazprombank), top universities and scientific centers all over the world.